IMPLEMENTASI AKAD MUKHABARAH DALAM MENINGKATKAN PRODUKSI PADI: STUDI KASUS DI KAMPUNG BARU, DESA KERTAMUKTI, KECAMATAN CIPATAT - Rohmat, Dede Saepul; Tunggara, Imam (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2024)
Akad Mukhabarah is a collaboration between landowners and cultivators, where landowners provide land to be planted and maintained by farmers with a mutually agreed share of the proceeds. In Kampung Baru, Kertamukti Village, this rice field cultivation cooperation is known as